The Construction of Multicultural Islamic Education: Harmonizing Sharia and the Nyongkolan Custom in Lombok - Hamdan Hamdan (Al-Munawwarah : Jurnal Pendidikan Islam, 2025)
This study aims to analyze the construction of multicultural Islamic education through the harmonization of Islamic Sharia and Nyongkolan customs among the Sasak community in Lombok. Nyongkolan is a traditional wedding procession where the bride and groom are paraded from the groom’s residence to the bride’s family home. While it is culturally rich, it often triggers social tension if not aligned with Sharia values. Utilizing a descriptive qualitative method with a case study approach, data were gathered through participatory observation, in-depth interviews with religious leaders (Tuan Guru), cultural figures, and tradition practitioners, as well as documentation. The results indicate that the Nyongkolan tradition in Lombok has undergone a process of Islamization and recontextualization. Islamic values, such as brotherhood (ukhuwah), charity, and respect for social entities, are integrated into the cultural ritual. This pattern of harmonization establishes an informal model of multicultural Islamic education within the community, fostering tolerance, inclusiveness, and conflict resolution based on local wisdom. The study concludes that the cultural accommodation within Nyongkolan serves as empirical evidence that Islamic Sharia and local customs can coexist dynamically without diminishing their respective identities.